2017
DOI: 10.1093/mnrasl/slx050
|View full text |Cite
|
Sign up to set email alerts
|

L1157-B1, a factory of complex organic molecules in a solar-type star-forming region

Abstract: We report on a systematic search for oxygen-bearing Complex Organic Molecules (COMs) in the Solar-like protostellar shock region L1157-B1, as part of the IRAM Large Program "Astrochemical Surveys At IRAM" (ASAI). Several COMs are unambiguously detected, some for the first time, such as ketene H 2 CCO, dimethyl ether (CH 3 OCH 3 ) and glycolaldehyde (HCOCH 2 OH), and others firmly confirmed, such as formic acid (HCOOH) and ethanol (C 2 H 5 OH). Thanks to the high sensitivity of the observations and full coverag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(159 citation statements)
references
References 29 publications
6
152
0
1
Order By: Relevance
“…The most studied ones are the hot corino sources, of which the prototype and best studied one is IRAS16293-2422(e.g., van Dishoeck et al 1995Ceccarelli et al 2000a;Jaber et al 2014;Jørgensen et al 2016). iCOMs are present in large quantities also in the shocks created by the outflows from Solar-like protostars, but also here studies exist only toward a very limited number of sources (e.g., Requena-Torres et al 2007;Arce et al 2008;Codella et al 2015;Lefloch et al 2017a). Interestingly, iCOMs are present in the lukewarm clouds of the Galactic Center (Requena- Torres et al 2006), likely due to the widespread shocks in the region.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…The most studied ones are the hot corino sources, of which the prototype and best studied one is IRAS16293-2422(e.g., van Dishoeck et al 1995Ceccarelli et al 2000a;Jaber et al 2014;Jørgensen et al 2016). iCOMs are present in large quantities also in the shocks created by the outflows from Solar-like protostars, but also here studies exist only toward a very limited number of sources (e.g., Requena-Torres et al 2007;Arce et al 2008;Codella et al 2015;Lefloch et al 2017a). Interestingly, iCOMs are present in the lukewarm clouds of the Galactic Center (Requena- Torres et al 2006), likely due to the widespread shocks in the region.…”
Section: Introductionmentioning
confidence: 65%
“…It is an isolated Class 0 source of intermediate mass associated with the infrared source IRAS 23011+6126. Its luminosity is L 100 ☉ and its mass is M 35 ☉ (Lefloch et al 1996;Crimier et al 2009). CepE drives an exceptionally powerful outflow, the southern lobe of which is terminated by the Herbig-Haro object HH377 (Lefloch et al 1996(Lefloch et al , 2015.…”
Section: Cepementioning
confidence: 99%
See 2 more Smart Citations
“…Previous observations revealed that in B1 the jet impacts caused erosion of the grain cores and ices, producing large quantities of gaseous SiO (∼10 −7 ; Gueth et al 1998) Lefloch et al 2017). Hence, L1157-B1 provides us with a perfect place to study the reactions occurring when previously frozen species are injected into the gas, as their relative abundance evolution depends on the relative efficiency of the various reactions.…”
Section: Or On Interstellar Dust Grainsmentioning
confidence: 99%